(untitled) (Research, Society and Development, 2021)
Weight training is becoming one of the considerable risk factors for the existence of Urinary Incontinence (UI) in women who practice physical activity. This is due to greater efforts, as is the case of this modality, which can generate an increase in intra-abdominal pressure, overloading the pelvic organs and, consequently, causing damage to the muscles responsible for these organs, thus causing UI, in addition , the excess of this exercise can cause fatigue of the pelvic floor muscles, thus predisposing to UI. Thus, the study sought information in bibliographic references of practical studies and studies that were carried out through online questionnaires about the prevalence of urine loss in women who develop bodybuilding, thus having a sample number considered to reach a conclusion about the problem proposed. According to a study, we can observe that the vast majority of urine loss prevailed in some cases and that it generates discomfort and directly influences the quality of life of women. Thus, the study found that, despite the few women studied, being 918 practitioners of the activity, of these 152 had urine loss, so there is a need to emphasize that professionals working in this area should develop better strategies and more appropriate ways in the training planning of the students who practice bodybuilding.